Ultra-low warpage high interlayer strength nylon elastomer modified material for 3D printing and preparation method and application thereof

CN123004151APending Publication Date: 2026-10-30XIAOGAN ESUN NEW MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202611247054.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0008]本发明提出一种3D打印用超低翘曲高层间强度尼龙弹性体改性料及其制备方法,解决现有技术中常规尼龙弹性体打印材料难以满足低翘曲、高层间强度、高回弹、易打印的性能协同的缺陷

Benefits of technology

本发明所述改性材料通过向尼龙弹性体中添加共聚PEBA及热塑性弹性体,通过选择共聚PEBA中特定的第三单体及共聚比例,协同热塑性弹性体及相容剂的共同作用,实现兼顾低翘曲、高层间强度、高回弹、易打印的综合性能,用于3D打印制备打印耗材具有广阔的应用前景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application provides an ultralow-warp high-interlayer-strength nylon elastomer modified material for 3D printing and a preparation method and application thereof; the modified material comprises, in parts by mass, nylon elastomer 78.4-93.7 parts, copolymerized PEBA 1-5 parts, thermoplastic elastomer 4-10 parts, compatilizer 1-5 parts, lubricant 0.1-1 part and antioxidant 0.2-0.6 part; the copolymerized PEBA is obtained by polycondensation of polyamide hard segments, polyether soft segments and third monomer blocks; the copolymerized PEBA and the thermoplastic elastomer are added into the nylon elastomer, the specific third monomer and the copolymerization ratio in the copolymerized PEBA are selected, and the thermoplastic elastomer and the compatilizer are used in combination to realize the comprehensive performance of low warping, high interlayer strength, high resilience and easy printing, and the application prospect is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of 3D printing materials technology, specifically to modified nylon elastomers with ultra-low warpage and high interlayer strength for 3D printing, their preparation methods, and applications. Background Technology

[0002] Nylon elastomers are a common name for polyamide-based thermoplastic elastomers, abbreviated as TPAE. They refer to thermoplastic semi-crystalline copolymers composed of rigid polyamide hard segments and flexible polyether or polyester soft segments. In polyether block amide (PEBA), the soft segment refers specifically to the polyether; PEBA is the most widely used type of nylon elastomer.

[0003] Nylon elastomer (TPAE) possesses high resilience, excellent low-temperature toughness, and resistance to bending fatigue. Its overall performance surpasses that of flexible consumables such as thermoplastic polyester elastomer (TPEE) and thermoplastic polyurethane elastomer (TPU), making it an ideal substrate for high-end FDM flexible 3D printing. It is widely used in fields such as drones, sports equipment, medical protective equipment, and electronic packaging. However, currently available commercial nylon elastomer printing filaments have significant technical defects, which restrict their industrial-scale application.

[0004] On the one hand, the FDM layer-by-layer deposition molding method means that the interlayers rely solely on surface wetting and hydrogen bonding. Nylon elastomer melt has high viscosity and poor fluidity. Rapid cooling leads to insufficient molecular chain entanglement, which easily results in significant anisotropy and weak interlayer strength in the printed products. Existing modification technologies cannot effectively improve the interlayer bonding force, resulting in low Z-axis strength and easy interlayer fracture under stress.

[0005] On the other hand, conventional nylon elastomers have high molecular chain regularity, fast crystallization rate, and large cooling shrinkage rate. During the FDM layer-by-layer cooling molding process, residual internal stress is easily generated. In addition, their low molecular polarity results in low bonding strength with polar substrates (such as metals and glass), ultimately leading to defects such as warping, edge lifting, dimensional deviation, and bottom delamination in the finished product. Existing improvement solutions mostly use inorganic fillers (such as CN109880358A, CN110079010A), short fibers (CN121271100A), or add low-melting-point polymers (such as CN108641197A). Inorganic fillers and short fibers can easily damage the material's elasticity and clog the printing nozzles, while low-melting-point polymers can affect the interlayer strength of the printed parts, making it difficult to simultaneously meet the requirements of low warping, high interlayer strength, and high resilience.

[0006] International publication WO2008006987A1 describes a method to reduce the crystallinity of polyamide by introducing cycloaliphatic diamines and non-aliphatic diacid monomers to achieve high transparency. However, the proportion of cycloaliphatic diamines added in this publication is as high as 70%, resulting in a glass transition temperature of ≥75℃ for the prepared polyamide. This will inevitably have an adverse effect on the resilience and low-temperature toughness of the polyamide. In addition, the application effect of the polyamide material prepared in this publication in the field of FDM 3D printing is unknown, and the introduction of too many cycloaliphatic diamines into the polyamide structure will lead to high prices and limited applications.

[0007] In summary, conventional nylon elastomer printing materials in existing technologies suffer from severe warping and low interlayer strength. Low-warping modified products generally suffer from compromised elasticity and mechanical properties, failing to achieve a synergistic effect of low warping, high interlayer strength, high resilience, and ease of printing. Therefore, there is an urgent need in this field to develop a nylon elastomer 3D printing filament that balances dimensional stability, interlayer bonding strength, high elasticity, and good processability. Summary of the Invention

[0008] This invention proposes a modified nylon elastomer material with ultra-low warpage and high interlayer strength for 3D printing and its preparation method, which solves the problem that conventional nylon elastomer printing materials in the prior art cannot meet the performance synergy of low warpage, high interlayer strength, high resilience and easy printing.

[0009] The technical solution of this invention is implemented as follows: The first aspect of the present invention is to provide a modified nylon elastomer material with ultra-low warpage and high interlayer strength for 3D printing, comprising, by weight: 78.4 to 93.7 parts of nylon elastomer, 1 to 5 parts of copolymer PEBA, 4 to 10 parts of thermoplastic elastomer, 1 to 5 parts of compatibilizer, 0.1 to 1 part of lubricant, and 0.2 to 0.6 parts of antioxidant; The copolymer PEBA is formed by block condensation of polyamide hard segments, polyether soft segments, and a third monomer, with the molar proportion of the third monomer being ≤14%. The third monomer is selected from at least one of 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedimethylamine, 1,3-cyclohexanedimethylamine, 2-methyl-1,5-pentanediamine, 4,4'-diaminodicyclohexylpropane, neopentanediamine, and m-phenylenediamine.

[0010] Furthermore, the polyamide hard segment is selected from at least one of PA66, PA612, PA1010, PA1012, PA11, and PA12; And / or, the polyether soft segment is selected from at least one of polytetrahydrofuran ether diol and polypropylene glycol.

[0011] Furthermore, the glass transition temperature of the copolymerized PEBA is ≤-40℃.

[0012] Furthermore, the hardness of the nylon elastomer is less than 65D, and its resilience is not less than 60%.

[0013] Furthermore, the thermoplastic elastomer is at least one of thermoplastic polyester elastomer and thermoplastic polyurethane elastomer.

[0014] Furthermore, the compatibilizer is selected from at least one of TPU-g-MAH, TPEE-g-MAH, TPU-g-GMA, and SEBS-g-MAH; And / or, the antioxidant is selected from at least one of hindered phenolic antioxidants and phosphite antioxidants; And / or, the lubricant is selected from at least one of calcium stearate, silicone masterbatch, ethylene bisoleamide, ethylene bisstearamide, and oxidized polyethylene wax.

[0015] A second aspect of the present invention is to provide a method for preparing the modified nylon elastomer described in the first aspect, wherein measured components are mixed evenly and then melt-extruded and granulated to obtain the modified material.

[0016] A third aspect of the present invention is to provide a 3D printing filament prepared from the nylon elastomer modified material described in the first aspect, or prepared by the preparation method described in the second aspect of claim 7.

[0017] A fourth aspect of the present invention is to provide a 3D printed article obtained by FDM printing using the 3D printing filament described in the third aspect.

[0018] A fifth aspect of the invention is to provide the application of the 3D printed articles described in the fourth aspect in the fields of drones, sports equipment, medical protective equipment, or electronic packaging.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The modified material described in this invention achieves comprehensive performance by adding copolymerized PEBA and thermoplastic elastomer to nylon elastomer. By selecting a specific third monomer and copolymerization ratio in the copolymerized PEBA, and through the combined effect of thermoplastic elastomer and compatibilizer, it achieves low warpage, interlayer strength, high resilience, and easy printing. It has broad application prospects for 3D printing consumables. Detailed Implementation

[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0021] This invention proposes a modified nylon elastomer material with ultra-low warpage and high interlayer strength for 3D printing. The components, by mass parts, include: 78.4-93.7 parts of nylon elastomer, 1-5 parts of copolymer PEBA, 4-10 parts of thermoplastic elastomer, 1-5 parts of compatibilizer, 0.1-1 parts of lubricant, and 0.2-0.6 parts of antioxidant. The copolymer PEBA is formed by block condensation of polyamide hard segments, polyether soft segments, and a third monomer, with the molar proportion of the third monomer being ≤14%. The third monomer is selected from at least one of 1,4-cyclohexanedicarboxylic acid (1,4-CHDA), 1,3-cyclohexanedicarboxylic acid (1,3-CHDA), 1,4-cyclohexanedimethylamine (1,4-BAC), 1,3-cyclohexanedimethylamine (1,3-BAC), 2-methyl-1,5-pentanediamine (MPMD), 4,4'-diaminodicyclohexylpropane (PACP), neopentanediamine, and m-phenylenediamine (MXDA).

[0022] The modified material of this invention introduces a specific proportion of a third comonomer into copolymerized PEBA, significantly reducing the crystallinity and crystallization rate of PEBA by disrupting the regularity of the PEBA molecular chains. This, in turn, reduces the internal stress generated during the FDM layer-by-layer cooling molding process, decreases material shrinkage, and helps reduce printing warpage. Compared to traditional PEBA, it features less warpage, higher dimensional accuracy, and excellent low-temperature toughness. The modified material utilizes the synergistic effect of thermoplastic elastomers and compatibilizers. The thermoplastic elastomers enhance melt polarity and promote molecular diffusion and entanglement between printing layers; the compatibilizers eliminate interphase interface defects, and the increased polarity of the blend enhances adhesion to the substrate. Through these multiple effects, the modified material achieves a balance of low warpage, high interlayer strength, and high resilience.

[0023] The modified material described in this invention reduces the water absorption rate and widens the melt processing window by introducing a specific proportion of a third comonomer into the copolymerized PEBA, which can improve the interlayer bonding effect in FDM printing to a certain extent while retaining the core advantage of PEBA's high resilience. However, simple copolymer modification still suffers from poor heat resistance and insufficient interlayer strength, and is also very costly. Therefore, adding a small amount of copolymerized PEBA to nylon elastomer can improve printing warpage while controlling costs. In addition, because the crystallization rate of the composite material is slowed down and the molten state residence time is longer, the molecular chains in the printing layers diffuse and entangle more fully, resulting in a significant improvement in the interlayer strength. Since the added copolymerized PEBA and thermoplastic elastomer both have high resilience and the total addition amount is not high, it will not have a significant negative impact on the resilience of the nylon elastomer, so that the final 3D printing nylon elastomer filament has the characteristics of low warpage, high interlayer strength, and high resilience.

[0024] In some embodiments of the present invention, printed parts prepared from filaments made from the above modified materials exhibit properties such as warpage less than 0.30 mm (250 mm flat plate warpage test), springback greater than 60% (ASTM D2632), and Z-axis tensile strength and Z-axis elongation at break greater than 9 MPa and 180% respectively (GB / T 1040.2-2006). This meets the application requirements for consumables in the fields of unmanned aerial vehicles, sports equipment, medical protective equipment, or electronic packaging.

[0025] The copolymer PEBA of this invention is formed by block condensation polymerization of polyamide hard segments, polyether soft segments, and a third monomer, i.e., by co-condensation polymerization of the aforementioned hard segments, soft segments, and small molecule monomers in a specific ratio. Preferably, the glass transition temperature of the copolymer PEBA is ≤-40℃.

[0026] In a preferred embodiment, the polyamide hard segment is selected from at least one of PA66, PA612, PA1010, PA1012, PA11, and PA12; and the polyether soft segment is selected from at least one of polytetrahydrofuran ether glycol (PTMEG) and polypropylene glycol (PPG).

[0027] It is understood that the nylon elastomer is composed of flexible polyether segments and rigid polyamide. Preferably, the hardness of the nylon elastomer is less than 65D and the resilience is not less than 60%.

[0028] In a preferred embodiment, the thermoplastic elastomer is at least one of thermoplastic polyester elastomer (TPEE) and thermoplastic polyurethane elastomer (TPU). The compatibilizer is selected from at least one of TPU-g-MAH, TPEE-g-MAH, TPU-g-GMA, and SEBS-g-MAH.

[0029] In a preferred embodiment, the antioxidant is selected from common antioxidants, including but not limited to at least one of hindered phenolic antioxidants and phosphite antioxidants; the lubricant is selected from at least one of calcium stearate, silicone masterbatch, ethylene bisoleamide, ethylene bisstearamide, and oxidized polyethylene wax.

[0030] In some preferred embodiments of the present invention, the printed parts prepared by using filaments modified with the above-mentioned components have a warpage of less than 0.20 mm (250 mm flat plate warpage test), a springback rate greater than 65% (ASTM D2632), and a Z-axis tensile strength and Z-axis elongation at break greater than 14 MPa and 220% (GB / T 1040.2-2006), respectively. More preferably, printed parts with a warpage of less than 0.15 mm, a springback rate greater than 68%, and a Z-axis tensile strength and Z-axis elongation at break greater than 14.5 MPa and 230%, respectively, can be obtained.

[0031] This invention also provides a method for preparing printing filaments from the above modified materials. The components are weighed according to a specified ratio, mixed for 5-10 minutes, and the twin-screw extrusion temperature is adjusted to 140℃-230℃. The mixture is then melt-extruded, granulated, and dried to produce a modified composite material. The modified composite material is then extruded using a single screw to produce 3D printing filaments, wherein the cooling water temperature is not higher than 45℃, the traction speed is not higher than 85m / min, and the filament diameter deviation is controlled to be ≤±0.05mm, and the roundness is ≤0.05mm.

[0032] The present invention also provides a 3D printed part, which is obtained by FDM printing from the above printing filament, and the printing conditions are: nozzle temperature 220~260℃, base plate temperature 35~50℃, fan 10~100%.

[0033] This invention also provides the application of the above-mentioned printing filaments in the preparation of consumables such as drones, sports equipment, medical protective equipment or electronic packaging through 3D printing. By using common FDM printing, the deposition path, filling ratio and filling structure of the modified material can be controlled to achieve the preparation of the target consumables and meet the requirements of low warpage, interlayer strength and high resilience.

[0034] The following are preferred embodiments of the present invention. Unless otherwise specified, the reagents used in the embodiments are commercially available standards in the art, and the experimental methods used are methods that are well mastered by those skilled in the art.

[0035] The raw material information used in the embodiments of this invention is as follows: 1) Nylon elastomer-1: Arkema, France, PEBAX 5533 SA 01, hardness 50D, resilience 73%.

[0036] 2) Nylon elastomer-2: Shandong Dongchen Ruisen New Material Technology Co., Ltd., TPA12-40, hardness 38D, resilience 68%.

[0037] 3) Nylon elastomer-3: Shandong Xinyuan Chemical, KHX7063, hardness 63D, resilience 66%.

[0038] 4) Copolymer PEBA-1: hard segment is PA12, soft segment is PTMEG 2000, third monomer is MXDA+1,3-CHDA, total copolymerization ratio is 10 mol%, hardness is 48D, Tg = -55℃.

[0039] 5) Copolymer PEBA-2: hard segment is PA1012, soft segment is PTMEG 2000, third monomer is 1,4-CHDA, copolymerization ratio is 12mol%, hardness is 46D, Tg = -56℃.

[0040] 6) Copolymer PEBA-3: hard segment is PA11, soft segment is PTMEG 1000, third monomer is MPMD, copolymerization ratio is 8 mol%, hardness is 39D, Tg = -52℃.

[0041] 7) Copolymer PEBA-4: hard segment is PA12, soft segment is PTMEG 2000, third monomer is PACP, copolymerization ratio is 5 mol%, hardness is 61D, Tg = -57℃.

[0042] 8) Copolymer PEBA-5: hard segment is PA612, soft segment is PTMEG 2000, third monomer is 1,3-BAC, copolymerization ratio is 10 mol%, hardness is 48D, Tg = -54℃.

[0043] 9) Ordinary PEBA: hard segment is PA12, soft segment is PTMEG 2000, hardness is 49D, Tg = -58℃.

[0044] 10) Copolymer PEBA-6: hard segment is PA12, soft segment is PTMEG 2000, third monomer is MXDA+1,3-CHDA, copolymerization ratio is 20 mol%, hardness is 50D, Tg = -50℃.

[0045] 11) TPU-1: Huafeng New Materials, HF-4395AU, hardness 95A.

[0046] 12) TPU-2: Huafeng New Materials, HF-4390AU, hardness 90A.

[0047] 13) TPU-3: Wanhua Chemical, GTZH64, hardness 64D.

[0048] 14) TPEE-1: DuPont Hytrel 5526, hardness 51D.

[0049] 15) TPEE-2: Sichuan Chenguang Kexin Plastics Co., Ltd., H4040, hardness 38D.

[0050] 16) TPEE-3: Xinjiang Lanshan Tunhe Technology Co., Ltd., TH3055, hardness 52D.

[0051] 17) SEBS-g-MAH: Kraton, USA, FG1901.

[0052] 18) TPU-g-MAH: Shenzhen Wansuyuan Rubber & Plastics Co., Ltd., MY134.

[0053] 19) TPEE-g-MAH: Dongguan Yutai Plastics Co., Ltd., Yutai 255.

[0054] 20) EBS: Japanese florist, KAOWAX EB-FF.

[0055] 21) EBO: Mitsubishi Chemical, Cplasa L 102P.

[0056] 22) OPE: GMT Chemicals, South Korea, GMT-1816.

[0057] 23) Silicone masterbatch: Hangzhou Kaijie Plastics Technology Co., Ltd., KJ-A01.

[0058] 24) Calcium stearate: Singapore San Yi, SAK-CS-P.

[0059] 25) Antioxidant 1010: BASF, Irganox® 1010.

[0060] 26) Antioxidant 1098: RIANORON, RIANOX® 1098.

[0061] 27) Antioxidant 168: BASF, Irgafos® 168.

[0062] The above-mentioned PEBA copolymers are obtained through melt polycondensation (taking PEBA-1 copolymer as an example): Step 1: Synthesis of dicarboxylate-terminated copolymer PA12 oligomer. A small amount of MXDA and 1,3-CHDA were pre-salted with an aqueous solution of dodecanoic acid. Laurolactam, hypophosphite, and antioxidant 1098 were added in stoichiometric amounts, ensuring an excess of dodecanoic acid. Under nitrogen protection, the reaction was first carried out at 180–210 °C for 1–2 h, followed by dehydration condensation at 230–240 °C for 2–3 h. The end-carboxyl group content was controlled by sampling to obtain a dicarboxylate copolymeric amide prepolymer with Mn = 1500–2500.

[0063] Step 2: Block polycondensation with PTMEG-2000. The above-mentioned dicarboxylated polyamide prepolymer and fully dried PTMEG-2000 are put into a high-pressure reactor. Under nitrogen protection, the mixture is first stirred and melted uniformly at 210~230℃. Then, 0.03~0.06wt% zirconium catalyst and compounded antioxidant are added. The temperature is raised to 240~252℃ and reacted for 2~4 hours. Gradual vacuum is applied to control the melt viscosity and molecular weight. The vacuum is then broken by nitrogen repressurization, and the mixture is pelletized underwater to finally prepare copolymerized PEBA particles.

[0064] Examples 1-8

[0065] The modified material compositions of Examples 1-8 are shown in Table 1.

[0066] Table 1:

[0067] Comparative Examples 1-9

[0068] The modified material compositions of Comparative Examples 1-9 are shown in Table 2.

[0069] Table 2:

[0070] Wire preparation: The components of the above-described embodiments and comparative examples were weighed according to the specified proportions, mixed for 10 minutes, and the twin-screw extrusion temperature was adjusted to 140~230℃. Modified material particles were then produced through melt extrusion, granulation, and drying. These particles were then extruded using a single screw to produce 3D printing filaments, with a cooling water temperature of 45℃, a traction speed of 85m / min, and the filament diameter deviation controlled to be ≤±0.05mm and roundness ≤0.05mm.

[0071] Test case

[0072] The filaments prepared in each embodiment and comparative example were dried at 60-80℃ for 4-8 hours and then printed using a Tuozhu P1S printer. The nozzle temperature was 220-260℃, the substrate temperature was 35-50℃, and the fan speed was 10-100%. All printing conditions were kept consistent. Standard samples were prepared according to the following standards, and then performance tests were conducted.

[0073] 1) Resilience: The infill density of the printed part is 30%, with mesh filling; tested according to ASTM D2632 standard, the test conditions are 23℃.

[0074] 2) Warpage Amount: The prepared filament is printed into a 250mm×250mm×2mm flat plate. After printing, it is cooled at room temperature for 2 hours. The flat plate is placed on a horizontal table, and the height of each of the four corners from the horizontal plane is measured. The maximum height is recorded as the warpage amount. Generally speaking, the larger the length and width of the printed flat plate, the greater the warpage amount of ordinary PEBA printing. Therefore, using a large-size part can amplify the warpage amount of the filament, making the test results more obvious.

[0075] 3) Tensile strength (Z-axis) and elongation at break (Z-axis): The maximum printing volume flow rate was 4 mm³ / s, the layer height was 0.2 mm, the fan ratio was 100%, all speed reduction settings were turned off, concentric filling was 100%, and the material was melted and deposited layer by layer along the Z-axis to form a standard tensile specimen. Testing was conducted according to GB / T 1040.2-2006 standard at a speed of 100 mm / min. The Z-axis tensile strength and Z-axis elongation at break reflect the interlayer strength of the FDM 3D printed filament. Generally, the higher the hardness, the higher the tensile strength of the nylon elastomer. Therefore, the Z-axis tensile strength of nylon elastomers with different hardnesses cannot be directly compared, while the Z-axis tensile strength of nylon elastomers with the same hardness can be compared. Therefore, the Z-axis elongation at break is used as a characterization of the toughness and interlayer bonding strength of the printed material.

[0076] 4) Hardness: Print the prepared wire into a 15mm×15mm×4mm part with 100% fill, and then measure it according to GB / T2411-2008.

[0077] The performance test results of the above embodiments and comparative examples are shown in Table 3.

[0078] Table 3:

[0079] As can be seen from the summary table of the test results above, the 3D printing nylon elastomer materials prepared in Examples 1 to 8 have a springback rate of over 60%, the warpage of the printed 250mm×250mm×2mm large sheet parts is ≤0.3mm, the Z-axis tensile strength is high (which varies depending on the material hardness), the Z-axis elongation at break is over 160%, and the overall performance is excellent.

[0080] Compared to Example 1, Comparative Example 1 did not add copolymer PEBA, while Comparative Example 2 added copolymer PEBA below the lower limit, lacking the effect of copolymer PEBA in improving resilience. At the same time, the resilience of TPU was significantly less than that of PEBA, resulting in a significant decrease in resilience. In addition, due to the low amount of copolymer PEBA added, its ability to regulate the crystallization rate of nylon elastomer was weakened, resulting in warpage >0.3mm. Furthermore, the Z-axis tensile strength and elongation at break both decreased to some extent.

[0081] Compared to Example 1, Comparative Example 3 added copolymer PEBA exceeding the upper limit. The addition of the third monomer MPMD led to a decrease in intermolecular hydrogen bonding. Due to the decrease in heat resistance and hardness of copolymer PEBA, the hardness of the composite material decreased, while the shrinkage rate increased. Ultimately, this resulted in an increase in the warpage of the composite material and a decrease in Z-axis tensile strength and elongation at break.

[0082] Compared to Example 1, Comparative Example 4 uses ordinary non-copolymer PEBA, which is a conventional nylon elastomer, similar to Comparative Example 1 and Comparative Example 2.

[0083] Compared to Example 1, the proportion of the third comonomer of PEBA used in Comparative Example 5 exceeded the upper limit, which had a negative impact. This was because the rigidity of the molecular chain increased significantly, the compatibility between the soft and hard phases deteriorated, and the material's resilience decreased significantly. At the same time, the melt viscosity increased, the processing temperature window narrowed, the interlayer wetting in 3D printing was insufficient, the anisotropy of the product intensified, and ultimately the interlayer bonding strength decreased and the warpage increased.

[0084] Compared to Example 1, the amount of TPU added in Comparative Example 6 was lower than the lower limit. Due to the lack of synergistic effect of TPU, the printing warpage of the composite material was slightly increased, and the Z-axis tensile strength and elongation at break were slightly decreased.

[0085] Compared to Example 1, the amount of TPU added in Comparative Example 7 exceeded the upper limit. Since the resilience of TPU is significantly less than that of PEBA, the resilience of the composite material decreased significantly.

[0086] Compared to Example 1, Comparative Example 8 did not add a compatibilizer. Due to the poor compatibility between nylon elastomer and TPU, interphase interface defects occurred. In addition, the lack of a compatibilizer to bond the printing substrate ultimately led to varying degrees of decrease in the resilience, warpage, and interlayer bond strength of the composite material.

[0087] Compared to Example 1, Comparative Example 9 did not contain copolymer PEBA, TPU / TPEE, or compatibilizer. Although its printing rebound rate was high, the warpage was significant due to the fast cooling and crystallization rate of the nylon elastomer and the large internal stress during layer-by-layer deposition. The interlayer bonding strength was also average.

[0088] It is understood that this invention, by adding copolymerized PEBA, TPEE or TPU, compatibilizers, etc., to conventional nylon elastomers and adjusting the proportions of each component to achieve synergistic effects, can prepare a nylon elastomer-modified composite material for 3D printing that possesses low warpage (≤0.3mm), high interlayer strength, and high resilience (≥60%). The reason is: The third comonomer can disrupt the molecular regularity of PEBA, reduce the overall crystallization rate, and release internal stress, which helps reduce the warpage of printed parts. However, low crystallinity does not necessarily lead to low warpage. When the copolymerization ratio of the third monomer exceeds a certain range, the rigidity of the molecular chain increases significantly, the compatibility between the soft and hard phases deteriorates, and the intermolecular hydrogen bonding decreases, which has the opposite effect and will have a negative impact on resilience, hardness, and interlayer strength. In addition, single copolymerized PEBA cannot achieve ultra-low warpage. The synergistic effect of TPEE, TPU, and compatibilizer is also required. TPU / TPEE increases melt polarity and promotes molecular diffusion and entanglement between printed layers; compatibilizer eliminates interphase interface defects, and the increased polarity of the blend can enhance adhesion to the substrate. The combination of these three factors achieves a synergistic effect of low warpage, high interlayer strength, and high resilience, which is something that existing technologies cannot anticipate.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A modified nylon elastomer material with ultra-low warpage and high interlayer strength for 3D printing, characterized in that, The components, by weight, include: 78.4-93.7 parts of nylon elastomer, 1-5 parts of copolymer PEBA, 4-10 parts of thermoplastic elastomer, 1-5 parts of compatibilizer, 0.1-1 part of lubricant, and 0.2-0.6 parts of antioxidant. The copolymer PEBA is formed by block condensation of polyamide hard segments, polyether soft segments, and a third monomer, with the molar proportion of the third monomer being ≤14%. The third monomer is selected from at least one of 1,4-cyclohexanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedimethylamine, 1,3-cyclohexanedimethylamine, 2-methyl-1,5-pentanediamine, 4,4'-diaminodicyclohexylpropane, neopentanediamine, and m-phenylenediamine.

2. The nylon elastomer modified material as described in claim 1, characterized in that, The polyamide hard segment is selected from at least one of PA66, PA612, PA1010, PA1012, PA11, and PA12; And / or, the polyether soft segment is selected from at least one of polytetrahydrofuran ether diol and polypropylene glycol.

3. The nylon elastomer modified material as described in claim 1, characterized in that, The glass transition temperature of the copolymerized PEBA is ≤-40℃.

4. The nylon elastomer modified material as described in claim 1, characterized in that, The hardness of the nylon elastomer is less than 65D, and its resilience is not less than 60%.

5. The nylon elastomer modified material as described in claim 1, characterized in that, The thermoplastic elastomer is at least one of thermoplastic polyester elastomer and thermoplastic polyurethane elastomer.

6. The nylon elastomer modified material as described in claim 1, characterized in that, The compatibilizer is selected from at least one of TPU-g-MAH, TPEE-g-MAH, TPU-g-GMA, and SEBS-g-MAH; And / or, the antioxidant is selected from at least one of hindered phenolic antioxidants and phosphite antioxidants; And / or, the lubricant is selected from at least one of calcium stearate, silicone masterbatch, ethylene bisoleamide, ethylene bisstearamide, or oxidized polyethylene wax.

7. The method for preparing the modified nylon elastomer material according to any one of claims 1-6, characterized in that, The measured components are mixed evenly, and then melt-extruded and granulated to obtain the final product.

8. A 3D printing filament, characterized in that, It is prepared from the nylon elastomer modified material according to any one of claims 1-6, or prepared by the preparation method according to claim 7.

9. A 3D printed product, characterized in that, The 3D printing filament described in claim 8 is obtained by FDM printing.

10. The application of the 3D printed article of claim 9 in the fields of drones, sports equipment, medical protection, or electronic packaging.

Citation Information

Patent Citations

  • Polypropylene wire material for 3D printing and preparation method thereof

    CN108641197A

  • Low-warpage enhanced PA material, preparation method thereof and application in 3D printing

    CN109880358A

  • Shape memory polymer alloy for fused deposition based 3D printing and preparation method of shape memory polymer alloy

    CN110079010A

  • High-strength, low-shrinkage and low-warpage reinforced polypropylene material based on 3D printing and preparation method of high-strength, low-shrinkage and low-warpage reinforced polypropylene material

    CN121271100A

  • Copolymers having amide units and ether units with improved optical properties

    WO2008006987A1